Star‐Shaped CuS Flat Nanoflakes Reinforced Ni(OH)2 Nanosheets for Enhanced Capacitance. Issue 40 (30th October 2018) - Reddy, B. Narsimha; Gupta, Govind; Ingole, Pravin P.
Abstract: Enhanced electrochemical capacitance of 2D‐nanosheets of Ni(OH)2 via reinforcement of star‐shaped CuS flat nanoflakes synthesized using in‐situ hydrothermal root is presented. Microscopic and structural characterization suggest the inclusion of CuS nanoflakes in the films. Reinforced CuS nanoflakes offer high surface area resulting into open‐sheet morphologies for Ni(OH)2 @CuS films; contrasting with the folded sheet structures attained for the neat Ni(OH)2 films. The remarkably high bulk (10 −3 S cm −1 ) conductivity of CuS enhances the conductivity and enable facile electron transport in the composites. Asymmetric supercapacitors constructed using Ni(OH)2 @CuS and graphite as the electrodes is noted to show specific capacitances of 642 Fg −1 at current density of 1 Ag −1, good rate capability and excellent cycling stability (86% capacitance retention at the end of 1000 cycles) relative to the neat Ni(OH)2 based supercapacitor cells that shows specific capacitance of 142 Fg −1 at the same current density. The direct contact of Ni(OH)2 with the conductive CuS nanoflakes and highly porous structures of Ni(OH)2 @CuS electrodes doubles the power densities of the Ni(OH)2 @CuS supercapacitors than Ni(OH)2 cells due to the low ion‐diffusion resistances for charging by ions from the electrolyte, afforded by the short diffusion pathways in the composites. Abstract : Reinforcement of Ni(OH)2 nanosheets with star‐shaped CuS nanoflakes leads to open‐sheet morphology of Ni(OH)2 @CuS with high surface area. Asymmetric supercapacitors constructed using Ni(OH)2 @CuS/graphite show specific capacitances of 642 Fg −1 at 1 Ag −1, good rate capability and cycling stability (86% capacitance retention after 1000 cycles) relative to the neat Ni(OH)2 based supercapacitor cells (142 Fg −1 at the same current density). This enhancement could be due to the direct contact of Ni(OH)2 with the conductive CuS nanoflakes and porous structures of Ni(OH)2 @CuS.